Effect of Gamification Element on Students Academic Performance In Mathematics In Basic Schools In Kwara State - Attah, Justina Ojoma; Ogunlade, Oyeronke Olufumilola; Falade, Ayotunde Atanda (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Gamification elements are excellent tools for promoting specific behaviors and enhancing academic performance. Method: The study used a non-equivalent group design using a 2x2x2 factorial, quasi-experimental pre-test-post-test format. The population for this study were all junior secondary students in Kwara State. The target population for this study was all junior secondary students in basic 2 (J.i.S 2) in Kwara-North. Two junior secondary schools in Kwara-North L.G.A. were chosen using a purposive sample technique because they have functional and well-equipped computer labs. School B was the control group, whereas School A was the experimental group. The two groups were intact classes. The instruments used for data collection were: The Mathematics Concepts Performance Test (MCPT) and the Quizalize gamification application. To ensure the reliability of the instrument, a pilot study was carried out the acquired results were tested using split-half Reliability coefficients, and a value of .89 was obtained. The findings of the study revealed that the adoption of gamification element has an impact on junior secondary school students’ mathematics performance, female students performed better than male students after the treatment was administered. It was recommended among others that the gamification element is successful in lowering the level of abstractness connected with the teaching and learning of some mathematical concepts at the junior secondary school level of education, mathematics teachers should incorporate it into the classroom.